Vacuum Tube Devices in Electronics - Davila, Leonel, author 644546 (Delhi, India : Research World, 2012)
In electronics, a vacuum tube, electron tube (in North America), or thermionic valve (elsewhere, especially in Britain) is a device that relies on the flow of electric current through a vacuum. Vacuum tubes may be used for rectification, amplification, switching, or similar processing or creation of electrical signals. Vacuum tubes rely on thermionic emission of electrons from a hot filament or cathode, that then travel through a vacuum toward a positively-charged anode or plate. Additional electrodes interposed between the cathode and anode can alter the current flow, making the device an amplifier. Vacuum tubes were critical to the development of electronic technology, which drove the expansion and commercialization of radio communication and broadcasting, television, radar, sound reproduction, large telephone networks, analog and digital computers, and industrial process control. Although some of these applications had counterparts using earlier technologies, such as the spark gap transmitter or mechanical computers, it was the invention of the triode vacuum tube and its capability of electronic amplification that made these technologies widespread and practical. For the most part vacuum tubes have been replaced by solid-state devices such as transistors and other semiconductor devices. Solid-state devices last much longer, are smaller, more efficient, more reliable, and cheaper than equivalent vacuum tube devices. However, tubes still find particular uses where solid state devices have not been developed or are not practical. Tubes are still produced for such applications and to replace those used in existing equipment such as high-power radio transmitters.